2012
DOI: 10.1002/stc.515
|View full text |Cite
|
Sign up to set email alerts
|

Field monitoring and numerical analysis of Tsing Ma Suspension Bridge temperature behavior

Abstract: It is important to take into account the effect of temperature in assessing the structural condition of bridges. However, very few quantitative studies have examined the temperature behavior of large-scale bridges because of their large size and complicated configuration. This paper, for the first time, investigates the temperature distribution and associated responses of a long-span suspension bridge-the 2132-m-long Tsing Ma Bridgethrough a combination of numerical analysis and field monitoring. With appropri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
103
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(116 citation statements)
references
References 17 publications
0
103
0
Order By: Relevance
“…Since their results were based on four days of data collected during summer, the interesting findings of this study are not necessarily indicative of the general thermal behaviour of the bridge. Probably the most comprehensive study on steel bridges to date in this field involved the use of finite element heat transfer analysis and field monitoring data to investigate the temperature distribution and thermal response of the Tsing Ma Bridge (suspension, 1377 m main span) in Hong Kong (Xia, Chen, Bao, & Xu, 2010;Xia, Chen, Zhou, & Xu, 2012;. Due to significant differences between the climates of Asian and European countries, the thermal performance results reported from studies on bridges in Asia might not be directly applicable to European bridges.…”
Section: Introductionmentioning
confidence: 99%
“…Since their results were based on four days of data collected during summer, the interesting findings of this study are not necessarily indicative of the general thermal behaviour of the bridge. Probably the most comprehensive study on steel bridges to date in this field involved the use of finite element heat transfer analysis and field monitoring data to investigate the temperature distribution and thermal response of the Tsing Ma Bridge (suspension, 1377 m main span) in Hong Kong (Xia, Chen, Bao, & Xu, 2010;Xia, Chen, Zhou, & Xu, 2012;. Due to significant differences between the climates of Asian and European countries, the thermal performance results reported from studies on bridges in Asia might not be directly applicable to European bridges.…”
Section: Introductionmentioning
confidence: 99%
“…It was strongly suggested that the nonuniform temperature distribution brought about by solar radiation should be considered in the design of curved bridges. Xia et al [46], for the first time, investigated the temperature distribution in a long-span suspension bridge-the 2132-m-long Tsing Ma Bridge-through finite element analysis. With appropriate assumptions, the bridge was divided into deck plate, section frame, and bridge tower, as shown in Figure 6.…”
Section: Finite Element Methodmentioning
confidence: 99%
“…Temperature has critical influence on the behavior of cable-stayed bridges, in particular long cable-stayed bridges and long suspension bridges [8,79]. Cao et al [12] comprehensively introduced the temperature distribution on girder, towers, and cables of a cable-stayed bridge and the behaviors of this bridge under temperature.…”
Section: Analysis and Modeling Of Loads And Environment Actions And Amentioning
confidence: 99%